2017
DOI: 10.1159/000477390
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty in the Cytodiagnosis of Mammary Analogue Secretory Carcinoma: Survey of 109 Cytologists with a Case Originating from a Minor Salivary Gland

Abstract: Background: Mammary analogue secretory carcinoma (MASC) of the salivary gland shows morphologic similarities and shares an immunophenotype and characteristic ETV6-NTRK3 translocation with secretory carcinoma of the breast. We present a buccal case of MASC along with a survey-based debate about its cytologic diagnosis by fine-needle aspiration (FNA). Case: FNA of the buccal nodule of a 58-year-old Japanese man was initially performed by 3 cytologists who gave different assessments of the Papanicolaou classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…11 MASC is difficult to diagnose on cytology because of the overlapping features and has previously been reported to mimic PTC, similar to our case, resulting in a misdiagnosis. [11][12][13][14][15] The intracytoplasmic and intraluminal eosinophilic secretions may be a helpful sign in addition to the enlarged vesicular nuclei with prominent nucleoli, which are typically seen in MASC and are not a feature of PTC. An additional finding of abundant granular to vacuolated cytoplasm is also a diagnostic clue of MASC in cytology specimens.…”
Section: Discussionmentioning
confidence: 99%
“…11 MASC is difficult to diagnose on cytology because of the overlapping features and has previously been reported to mimic PTC, similar to our case, resulting in a misdiagnosis. [11][12][13][14][15] The intracytoplasmic and intraluminal eosinophilic secretions may be a helpful sign in addition to the enlarged vesicular nuclei with prominent nucleoli, which are typically seen in MASC and are not a feature of PTC. An additional finding of abundant granular to vacuolated cytoplasm is also a diagnostic clue of MASC in cytology specimens.…”
Section: Discussionmentioning
confidence: 99%
“…They occasionally form cysts filled with white fluid. The cytological diagnosis of secretory carcinoma is difficult [69][70][71][72]. FNA may show cohesive epithelial clusters, sheets, papillary groups and/or dispersed cells with background colloid-like cystic debris.…”
Section: Non-neoplasticmentioning
confidence: 99%
“…15) [76][77][78][79][80]. AcCC-PCV may undergo metaplastic oncocytic or squamoid changes [72]. Some macrocysts may even contain scant mucin [2].…”
Section: Non-neoplasticmentioning
confidence: 99%
“…Although fine-needle aspiration may be performed during ultrasound evaluation, the cytology diagnosis for SC is poor. According to Kai et al, only 2 of 109 cytologists identified SC [11]. Immunohistochemistry and FISH studies using pathologic specimen can yield a definite diagnosis.…”
Section: Discussionmentioning
confidence: 99%